Transcriptomic profiling of hepatic tissues for drug metabolism genes in nonalcoholic fatty liver disease: A study of human and animals - Chen, Li; Chen, Lu; Li, Xu; Qin, Lin; Zhu, Yan; Zhang, Qianru; Tan, Daopeng; He, Yuqi; Wang, Yu-He (Frontiers in Endocrinology, 2023)
Abstract Background Drug metabolism genes are involved in the in vivo metabolic processing of drugs. In previous research, we found that a high-fat diet affected the transcript levels of mouse hepatic genes responsible for drug metabolism. Aims Our research intends to discover the drug metabolism genes that are dysregulated at the transcriptome level in nonalcoholic fatty liver disease (NAFLD). Methods We analyzed the transcriptome for drug metabolism genes of 35 human liver tissues obtained during laparoscopic cholecystectomy. Additionally, we imported transcriptome data from mice fed a high-fat diet in previous research and two open-access Gene Expression Omnibus (GEO) datasets (GSE63067 and GSE89632). Then, using quantitative real-time polymerase chain reaction (qRT-PCR), we cross-linked the differentially expressed genes (DEGs) in clinical and animal samples and validated the common genes. Results In this study, we identified 35 DEGs, of which 33 were up-regulated and two were down-regulated. Moreover, we found 71 DEGs (39 up- and 32 down-regulated), 276 DEGs (157 up- and 119 down-regulated), and 158 DEGs (117 up- and 41 down-regulated) in the GSE63067, GSE89632, and high-fat diet mice, respectively. Of the 35 DEGs, nine co-regulated DEGs were found in the Venn diagram (CYP20A1, CYP2U1, SLC9A6, SLC26A6, SLC31A1, SLC46A1, SLC46A3, SULT1B1, and UGT2A3). Conclusion Nine significant drug metabolism genes were identified in NAFLD. Future research should investigate the impacts of these genes on drug dose adjustment in patients with NAFLD. This study was registered with the Chinese Clinical Trial Registry (registration number: ChiCTR2100041714, http://www.chictr.org.cn/).